Pengaruh Kompensasi terhadap Kinerja Karyawan pada PT. Bintang Teknik Jakarta - Hasudungan, Zefanya; Lubis, Andriani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study investigates the influence of compensation on employee performance at PT Bintang Teknik in Jakarta, driven by concerns over unequal pay structures and unclear bonus systems, which may lower motivation and productivity. The primary objective is to analyze whether compensation both financial and non-financial significantly affects employee performance. A quantitative research design was employed using a saturated sampling method, involving all 50 employees as respondents. Data were collected through Likert-scale questionnaires and analyzed using validity and reliability tests, simple linear regression, Pearson correlation, coefficient of determination (R²), and t-test with the aid of SPSS 25. The results reveal a strong and significant relationship between compensation and employee performance, with a correlation coefficient of 0.654 and a determination coefficient (R²) of 0.428. The regression analysis indicates that an increase in compensation corresponds to a measurable increase in performance (Y = 21.187 + 0.748X), and the t-test confirms statistical significance (t = 5.993, p < 0.05). These findings support previous studies and reinforce the importance of fair and structured compensation systems in enhancing employee motivation, discipline, and accountability. The study concludes that compensation is a key strategic factor in driving employee performance and recommends continuous improvement of reward systems to support organizational goals.